Synthesis of Eicosapentaenoic Acid-enriched Phosphatidylcholine and its Effect on Pro-inflammatory Cytokine Expression - Baek, Jae Yeul; Na, Eun; Lim, Sun Y. (Combinatorial Chemistry & High Throughput Screening, 2022)
Aim and Objective: We synthesized eicosapentaenoic acid-enriched phosphatidylcholine (EPA-PC) and investigated its effect on the production of lipopolysaccharide (LPS)- induced cytokines in murine splenocytes. Material and Methods: The culture supernatants of splenocytes, which was exposed to EPA-PC along with LPS, was harvested to determine the production of cytokines [interleukin (IL)-4 , IL-5, IL-6, interferon (IFN)-γ, IL-2 and IL-12/IL-23(p40)]. Cytokines were measured using enzymelinked immunosorbent assay (ELISA). Results: The co-administration of EPA-PC with LPS resulted in a significantly lower IFN-γ expression than that observed with LPS alone (p < 0.01). Moreover, treatment with EPA-PC and LPS significantly decreased IL-2, IL-6 and IL-12/IL-23(p40) expression (p < 0.01). Coadministration of EPA-PC at a concentration of 0.3 μg/mL with LPS resulted in a higher IL-5 expression after 24 hr of treatment when compared to LPS alone (p < 0.05). Conclusion: These results suggest that EPA-PC is more effective in decreasing the expression of pro-inflammatory cytokines [IL-2, IFN-γ, IL-6 and IL-12/IL-23(p40)] upon induction of inflammation.
Keywords: PUFAs